STUDENTS PERCEPSTION ON TIKTOK AS A MEDIA FOR LEARNING ENGLISH SPEAKING SKILLS - Diana Rosa Agustina; Nabila; Muhammad Cikal Fakhrizal; Naf’an Tarihoran (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to analyze students’ perceptions of TikTok as a medium for learning English speaking skills. This research employed a quantitative approach with a descriptive design. The data were collected through a questionnaire distributed to 100 students of UIN Sultan Maulana Hasanuddin Banten using a five-point Likert scale. The findings reveal that students generally have positive perceptions of TikTok in supporting their speaking development. TikTok is considered helpful in improving speaking comprehension, vocabulary acquisition, pronunciation, imitation, and intonation. Among these aspects, vocabulary acquisition and intonation received the highest mean scores, indicating that TikTok effectively exposes students to authentic language use and natural speech patterns. Additionally, students tend to use imitation as a strategy to enhance their speaking skills through repeated exposure to video content. However, some neutral responses suggest that not all students fully utilize TikTok as a learning tool, as it is often used for entertainment purposes. In conclusion, TikTok has strong potential as an alternative and engaging learning medium for improving English speaking skills. Therefore, educators are encouraged to integrate TikTok into language learning activities to support more interactive and autonomous learning experiences.